The Judicial Commission's Supervisory Authority on the Behavior of Constitutional Court Judges - Pohwainyaan, Almendo Imanuel; Salmon, Hendrik; Irham, Muhammad (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Indonesia as a legal state upholds the principle of rule of law based on the 1945 Constitution, has institutions such as the Supreme Court, Constitutional Court, and Judicial Commission (KY) that play an important role in the justice system.Purposes of the Research: The purpose of this paper is to analyze and discuss the authority of the Judicial Commission in supervising constitutional judges and to analyze and explain the mechanism of Judicial Commission supervision of constitutional judges after Constitutional Court Decision Number: 005/PUU-TV/2006.Methods of the Research: The type of research used is normative juridical research. The problem approach used is a statutory approach and a conceptual approach. Sources of legal materials are primary legal sources and secondary legal materials. Procedures for collecting legal materials through literature studies. Processing and analyzing legal materials qualitatively.Findings of the Research: The results showed that to achieve a good and ideal judicial system, it can be realized by maintaining the objectivity and integrity of decisions and the behavior of judges in the judicial power, but currently the position and authority of the Judicial Commission (KY) as an external supervisory institution of the judiciary is still very weak due to restrictions by the Constitutional Court Decision Number: 005/PUU/IV-2006 and a narrow interpretation of the 1945 Constitution, so to answer the needs of the community, it is necessary to revise Law Number 18 of 2011 to explicitly emphasize the authority of KY in supervising all judges, including constitutional judges. KY must also be recognized as a state institution that is equal to the Supreme Court and the Constitutional Court in the Indonesian constitutional system, in accordance with the principle of checks and balances, to ensure effective, transparent and accountable supervision.